A Bibliometric Analysis on Fuzzy Approaches in Financial Management - Onar, Sezi Cevik; Cebi, Selcuk; Kahraman, Cengiz; Oztaysi, Basar (SPRINGER INTERNATIONAL PUBLISHING AG, 2024)
The increasing uncertainty and vagueness in the financial environment augmented the integration of fuzzy logic in financial decision-making processes. In the literature, various fuzzy approaches have been developed and used for managing financial problems. Yet, none of these methos have been proven to be dominant. The main objective of this study is to show the current fuzzy approach usage in financial management and highlight the impactful countries and journals and finally reveal the gaps in the literature. In this analysis, we also focus on the distribution of countries, journals, author keywords. We use Scopus database for the analysis, the analyze result shows that the earliest studies date back to 1986. Although after 2007, the number of studies has increased a decrease is faced in 2014. Yet, we see a significant increase in fuzzy usage in financial management literature after 2014. The field is mainly dominated by fuzzy journals. Journal of intelligent and fuzzy systems and expert systems with applications are the leading journals that publish studies in this field. This study emphasizes the changing landscape of fuzzy logic in financial management.
Keywords: Risk Assessment; Risk Analysis; Risk Management; Fuzzy Sets and Extensions; Risk Methodologies; Computer Science; Mathematics